Systems evaluation theory : a blueprint for practitioners evaluating complex interventions operating and functioning as systems - Renger, Ralph (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"Too often evaluation findings end of on the shelf! Why? Most interventions have many moving parts working together to achieve something each part cannot do independently. Unfortunately, many of the available evaluation approaches oversimplify this reality. A major reason for this is that evaluators do not have a blueprint to plan, and the associated methods to execute, an evaluation fit for this purpose. As such, they revert back to what they know how to do and make the method fit the problem. Consequently, the evaluation findings do not align with the stakeholders' intuition, so they are ignored. This book provides evaluators of all skill levels with a simple 3-step framework, Systems Evaluation Theory (SET), that will lead to more actionable recommendations because the methods better capture the reality in which interventions operate; that is as a system. The book first reviews the limitations of program evaluation approaches that pointed to a need for a different way of thinking, one grounded in systems. After defining a system, the book explains how SET is intentionally aligned to evaluate its two essential properties: interdependence and emergence. Individual chapters are dedicated to explaining how to execute each SET step. Throughout, the author draws on real-world examples and those from his own evaluations to help bridge the theory-practice divide. The reader is then shown how to use SET to develop actionable recommendations. The final chapters are devoted to understanding why programs should be considered subsystems and the value added of evaluating them using SET"-- Provided by publisher.
Keywords: Evaluation research (Social action programs); Evaluation.; System theory.; System analysis.; Social Science -- Research.; Social research and statistics.; elektronické knihy; electronic books